A (re) invenção de Inês de Castro no imaginário nordestino - Brito, Terezinha Maria de (2006)
The aim of this dissertation was to study the permanence of the myth of Inês de Castro on the Northeastern imaginary. To accomplish this purpose, it was analyzed the proverb Agora é tarde, Inês é morta (now is too late, Inês is dead), the chapters I, II, III of the poem Invenção de Orfeu (The invention of Orpheus), by Jorge de Lima and the sculpture La Victime, by Francisco Brennand. This project was initiated presenting the myth as a point of convergence for this triad, intercalating such different narratives. After that, it was verified the function and the trajectory of the myth of Inês de Castro on the oral tradition through the popular proverb. The poem of Jorge de Lima shows how the myth assumes multiple feminine faces and, finally, the analysis of the sculpture makes clear that it represents the concretization of the feminine love suffering evidenced on the proverb. Finally, having as source the concept of mitocrítica (myth critics), by Gilbert Durand, that allows to verify when a piece of art has a myth as its essence, and a lot of reading about the history of woman, the myth, the love and the oral tradition, it was possible to analyze how the (re)invention of Inês de Castro has been manifested on the Northeastern imaginary.